A general microwave synthesis of metal (Ni, Cu, Zn) selenide nanoparticles and their competitive interaction with human serum albumin. (16th March 2018) - Naveenraj, Selvaraj; Mangalaraja, Ramalinga Viswanathan; Krasulyaa, Olga; Syed, Asad; Ameen, Fuad; Anandan, Sambandam
Abstract : Simple microwave irradiation technique was used to synthesize a series of selenide nanoparticles (platelet-like NiSe nanoparticles, uniform CuSe nanorods, and distorted ZnSe nano-hexagons) and their competitive interaction with human serum albumin was studied. Abstract : A series of selenide nanoparticles (3 ± 1 nm sized platelet-like NiSe nanoparticles, uniform CuSe nanorods with a width of ∼12 nm and a length of 65 nm, and distorted ZnSe nano-hexagons with a side length of 12 ± 3.5 nm) were synthesized using a simple microwave irradiation technique using sodium selenite, hydrazine hydrate and starch as a selenide precursor, a reducing agent and a stabilizing agent, respectively. The morphologies and sizes of the as-synthesized nanoparticles were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM) and energy-dispersive X-ray spectroscopy (EDS) analysis. The interaction between this series of selenide nanoparticles (SNPs) and HSA was investigated using fluorescence and circular dichroism (CD) spectroscopy. The influencing factors such as the quenching type, binding stoichiometries, binding constants, and the free energy change determined using the fluorescence technique showed that SNPs spontaneously bound to HSA in a 1 : 1 ratio through non-fluorescent ground-state complex formation (static quenching mechanism). The binding constant values indicated that the binding forces were in descending order of NiSe > CuSe > ZnSe. The shift in the synchronous fluorescence spectra signified the involvement of the tryptophan moiety in the binding of SNPs with HSA. Based on the Förster theory of energy transfer, the distance between the donor (Trp residues) and the acceptor (SNPs) was obtained. Analysis of the far-UV and near-UV CD spectra of HSA suggested the effect of the SNPs on the secondary and tertiary structures of HSA. These investigations helped us to understand the interaction mechanisms between the nanoparticles and the protein molecule that interprets the pharmacokinetics of these nanoparticles while administering them as drugs.